Organic Solar Modules: Fully Doctor Bladed on Glass in Air. Issue 7 (5th April 2017) - Koppitz, Manuel; Hesse, Nicolas; Landerer, Dominik; Graf von Reventlow, Lorenz; Wegner, Eduard; Czolk, Jens; Colsmann, Alexander
Abstract: For future integration into building facades or overhead glazing, the direct deposition of organic solar modules on glass substrates in sheet‐to‐sheet processes may be more cost efficient than postproduction lamination. Complying with the special requirements for the deposition of the layer stack on glass substrates, we report on all‐doctor‐bladed organic solar modules yielding power conversion efficiencies of 4.5 and 3.6 % on photoactive areas of 1 and 20 cm 2, respectively. The bottom electrode is doctor bladed from a silver ink atop an adhesion enhancing primer. The top electrode is applied from silver nanowires, dispersed in poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), which thereby avoids any visible bus bars and reduces shading of the active layer. Importantly, all layers are deposited under ambient conditions by using only non‐chlorinated, eco‐compatible solvents. Abstract : Printable solar modules : All‐doctor‐bladed organic solar modules are fabricated in air by using eco‐compatible solvents. Opaque silver cathodes and transparent conductive polymer anodes are employed. Solar modules with photoactive areas of 20 cm 2 yield power conversion efficiencies of 3.6 %.